Investigating the Limitations of Integrated Tasks on Youth Entrepreneurship in Kurdistan Region - Nabaz Nawzad Abdullah; Masayu Binti Othman (Путеводитель предпринимателя)
The authors examined the importance of integrated tasks of entrepreneurship among young individuals in Kurdistan. The study aimed to evaluate the level of youth understanding of entrepreneurship. The data was collected from 242 youth and the frequencies have been used to measure the weights of the tasks from the youth perspective. The authors found ideas, training, knowledge, competencies, and skills are sufficiently important to youth entrepreneurship success. The study also indicated that young individuals in Kurdistan Region are not aware of the entrepreneurship dimensions as the tasks, but they still found it as an integrated part of entrepreneurship. The lack of creativity, initiative, and innovation among youth is found to be associated with poor quality of youth in identifying opportunities and risk–taking due to the lack of understanding and knowledge as pre–conditions to the business start–up.